A monitoring system for EPW safe use - Alsibai, Mohammed Hayyan; Nurul Nadia, Nor Hamran; Abdul Nasir, Abd Ghafar; Abdul Adam, Abdullah (Universiti Teknikal Malaysia Melaka (UTeM), 2018)
Electric Powered Wheelchair (EPW) can be considered as a special Electric Vehicle (EV) because it is used by senior citizens, disabled drivers/users who have special needs. Using manual or electric wheelchair independently rises up an important problem which is the lack of user monitoring. Wheelchair users are more subject to fatigue and emergency health situations. This paper presents an add-on smart monitoring system to help wheelchair users to use the wheelchair independently and safely. The system integrates health related sensors with computer, mobile phone and an alarm system. The tested prototype uses two sensors, namely, temperature sensor and heart beat sensor. The system is extendable and more sensors can be added. The temperature sensor is used to sense the body temperature which is a basic parameter for monitoring and diagnosing human health. Heartbeat sensor is used to measure the user Mean Arterial Pressure (MAP). It can be connected to a personal computer to show the cardiograph. Body temperature and MAP data are acquired by an embedded system and displayed on a Liquid Crystal Display (LCD). Data are also sent to the cloud for Internet of Things (IoT) monitoring. In emergency cases alarm signal is triggered. Moreover, a notification Email and SMS messages are sent to the people in charge of monitoring the user. The system was tested and validated as a real-time monitoring system.